The nature and value of knowledge three investigations - Pritchard, Duncan; Millar, Alan, Ph. D.; Haddock, Adrian (Oxford : Oxford University Press, 2010)
This volume comprises three distinct investigations into the relationship between the nature & the value of knowledge. The three sections look at 'knowledge & understanding', 'knowledge & recognition', & 'knowledge & action'. Each section is written by one of the authors in consultation with the other two.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Knowledge, Theory of